Effect of thermal processing on brominated 6FDA-DAM for effective propylene/propane separation - Xuan Huy Do; Que Thi Nguyen; Kim, Sejin; Lee, Albert S.; Baek, Kyung-Youl (ELSEVIER, 2021)
Developing polymeric membranes with propylene/propane separation performance surpassing the upper bound has been received much attention. Herein, a highly controlled thermal treatment process yielding microporous polyimide membranes made from dense brominated-polyimide membrane precursor via thermal debromination/cross-linking approach is demonstrated. We showed that facile thermal treatment could generate a narrow size distribution of micro-voids as well as covalent linkages between inter/intra polymer chains while the polyimide backbone structure remained intact. The thermally treated membranes were well-characterized by FTIR, TGA, WAXD, solid-state C-13 NMR and N-2 adsorption/desorption isotherm. Single gas propylene/propane (C3H6/C3H8) separation performance greatly improved in terms of both selectivity and permeability, surpassing the trade-off line while maintaining flexible membrane properties. A thermal cross-linking treatment at 380 degrees C for 5 h exhibited the best C3H6 permeability of 84.70 barrer and C3H6/C3H8 selectivity of 14.6 with high plasticization resistance.